Responding to Health System Failure on Tuberculosis in Southern Africa - Lauren Alecci Hartel; Abdo S. Yazbeck; Patrick L. Osewe (Taylor & Francis Group, 2018)
Abstract-The characteristics of tuberculosis (TB)-such as links to poverty, importance of patient actions, and prevalence of multisectoral drivers-require more from health systems than traditional medically oriented interventions. To combat TB successfully, health systems must also address social risk factors and behavior change in a multisector response. In this, many health systems are failing. To explore why, and how they can do better, we apply the Flagship Framework and its five "control knobs" (financing, payment, organization, regulation, and behavior) to the literature on TB control programs, focusing on the mining population of Southern Africa, among whom the incidence of TB is highest in the world. We conclude by recommending a patient-centered approach that broadens a system's engagement to a whole-of-health sector, whole-of-government response.